1983
DOI: 10.1161/01.hyp.5.2_pt_2.i184
|View full text |Cite
|
Sign up to set email alerts
|

Reflex-hemodynamic adjustments and baroreflex sensitivity during converting enzyme inhibition with MK-421 in normal humans.

Abstract: SUMMARY Invasive hemodynamic measurements and determination of baroreflex sensitivity were carried out in 12 mildly sodium-depleted normotensive volunteers in a randomized double-blind crossover study with a single dose of converting enzyme inhibitor, MK-421, and placebo. In supine humans at rest, MK-421 caused a reduction in blood pressure through a fall in total peripheral resistance and an increase in arterial compliance. Thus, MK-421 appears to dilate both resistance vessels and larger arteries. Cardiac ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 36 publications
5
26
0
1
Order By: Relevance
“…By that time, PCEA was dramatically decreased, PRA was increased and PA tended to decline. Systolic blood pressure was reduced by 9 ± 1 mm Hg (P < 0.05), a value in agreement with previous data in normotensive subjects (McGregor et al, 1981;Ibsen et al, 1983), but heart rate was not drug-affected. This lack of reflex tachycardia, a classical finding with all ACEIs, has led many authors to investigate the possible interference between ACEIs and BR function, since it could be accounted for either by an alteration of the BRS or by a modification of the BR set-point.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By that time, PCEA was dramatically decreased, PRA was increased and PA tended to decline. Systolic blood pressure was reduced by 9 ± 1 mm Hg (P < 0.05), a value in agreement with previous data in normotensive subjects (McGregor et al, 1981;Ibsen et al, 1983), but heart rate was not drug-affected. This lack of reflex tachycardia, a classical finding with all ACEIs, has led many authors to investigate the possible interference between ACEIs and BR function, since it could be accounted for either by an alteration of the BRS or by a modification of the BR set-point.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, only studies in normotensive subjects really allow an assessment of the effects of a given drug on baroreflex function. Recently, Ibsen et al (1983) have shown that in those conditions enalapril displaces to the left the BR set-point and induces a slight potentiation of BRS during activation by phenylephrine. However, the study was conducted in mildly sodium depleted subjects and in addition BRS to deactivation was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] The mechanism for this increased efficacy with chronic administration is not clear but may involve the kallikreinkinin system or production of vasodilatory prostaglandins. 16 One of the characteristics of ACEis is that they lower peripheral vascular resistance without causing a compensatory increase in heart rate [17][18][19][20] or changing baroreceptor activity. 21 They also show lack of reflex tachycardia 22 and cause inhibition of the normal tonic influence of Ang II on the sympathetic nervous system.…”
Section: Angiotensin-converting Enzyme Inhibitorsmentioning
confidence: 99%
“…In some studies (Petty and Reid 1981;Mancia et al 1982 ;Ibsen et al 1983 ), angiotensin converting enzyme inhibitors have been found to increase baroreflex sensitivity, while in other studies (Coleman et al 1974) captopril appeared to have no effect on the baroreflex sensitivity. Hatton et al (1981) reported that a converting enzyme inhibitor, SQ 20881, shifted the baroreflex curve toward the left without modifying reflex sensitivity, and concluded that this shift was responsible for the lack of reflex tachycardia.…”
Section: Discussionmentioning
confidence: 96%